Effect of transforming growth factor-beta1 on oestrogen metabolism in MCF-7 and MDA-MB-231 breast cancer cell lines. - Ee, Y.S.; Lai, L.C.; Reimann, K.; Lim, P.K. (Spandidos Publications, 1999)
Transforming growth factor-beta (TGF-beta) has been shown to inhibit the growth of mammary epithelial cells and may play a protective role in mammary carcinogenesis. In contrast, oestrogens promote the development of breast cancer. Oestrone sulphate (E1S) is a huge reservoir of active oestrogens in the breast being converted to the weak oestrogen, oestrone (E1), by oestrone sulphatase. E1 is reversibly converted by oestradiol-17beta hydroxysteroid dehydrogenase to the potent oestrogen, oestradiol (E2). The aim of this study was to assess the effect of the TGF-beta1 isoform on growth and oestrogen metabolism in the hormone-dependent MCF-7 and hormone-independent MDA-MB-231 human breast cancer cell lines. The results showed that TGF-beta1 significantly inhibited cell growth and stimulated the conversion of E1S to E1 and E1 to E2 in the MCF-7 cell line. In the MDA-MB-231 cell line TGF-beta1 significantly stimulated cell growth and inhibited the interconversions between E1 and E2. In conclusion, the growth inhibitory effect of TGF-beta1 on the MCF-7 cell line would appear to confer a protective effect in breast cancer. However, its ability to increase the amount of E2 would increase the risk of breast cancer. Which of these effects predominates in vivo remains to be explored. The growth stimulatory effect of TGF-beta1 on the MDA-MB-231 cell line probably acts through a mechanism independent of the effect of TGF-beta1 on oestrogen concentrations since this cell line is hormone unresponsive.